Determinants of Service Behavior of Customer Contact Personnel in Local Authority - Adhikari, Shiva Raj (KIC International Journal of Social Science and Management, 2022)
Determinants of service behavior of customer contact personnel are essential issues in the service or public organization. This research investigates 396 frontline employees of five local authorities in Kathmandu Valley. The researcher examines the relationships among service behavior, role stress, organizational commitment, customer orientation, and job satisfaction. The factors that influence the service behavior of CCP in the local authority are discussed in depth. The study’s significant findings demonstrated an overall strong association of the set of independent variables with the dependent variable, service behavior. These four factors have positively influenced the service behavior of CCP of a local authority in Kathmandu Valley.